Kompleksitas Yurisdiksi dan Pilihan Hukum dalam Perjanjian Kerja Lintas Batas: Studi Perlindungan Pekerja Remote Internasional di Indonesia - Dila Nurul Maghfira Arrahman (Advances In Education Journal, 2025)
The post-pandemic rise of borderless workforces has introduced jurisdictional complexities in cross-border employment agreements, particularly for Indonesian remote workers employed by foreign entities without local presence. This study aims to examine the characteristics of such employment relationships, the enforceability of foreign choice-of-law clauses under Indonesian public order principles, and competent dispute resolution forums. Employing a normative legal approach, data were collected through conceptual analysis of statutes, international conventions, and academic literature, including UU Ketenagakerjaan and ILO standards. Findings reveal that subordination tests reclassify "independent contractors" as employees entitled to protections; foreign choice-of-law clauses are void if violating mandatory rules via lex loci laboris; and while the Industrial Relations Court holds jurisdiction, enforcement challenges persist absent assets or bilateral agreements. This underscores the need for Employer of Record platforms and policy harmonization to safeguard vulnerable workers, fostering equitable globalization.